Diagnostic Utility of the Milan System for Reporting Salivary Gland Cytology in a Tertiary Hospital of Western Nepal - Adhikari, Milan; Ghimire, Pragya Gautam; Shrestha, Richa; Baidya, Pooja; Bhandari, Shama (Journal of Nepalgunj Medical College, 2023)
Introduction: Salivary gland Fine Needle Aspiration Cytology is a well-established pre-operative diagnostic tool done routinely worldwide. Heterogeneity of salivary gland lesions makes Aspiration cytology diagnosis challenging for most cytopathologists. Milan system for reporting salivary gland cytology is a six tier reporting system developed to minimize inter-observer variability, thus to enhance reproducibility of cyto-diagnosis. Aims: To study diagnostic utility of Milan System for Reporting Salivary Gland Cytology. Methods: This is a one-year hospital based study done at Department of Pathology, Nepalgunj Medical College Teaching Hospital. It included 46 cases of salivary gland Cytology. Biopsy was available for 22 of them. Fine Needle Aspiration Cytology cases were reported as per the Milan System and subsequently correlated with gold standard histopathology. Results: Age of patients ranged from 8-79 years with submandibular and parotid gland being the commonly involved ones. Most cases were in Category II (Non Neoplastic) according to Milan System for Reporting Salivary Gland Cytology (48%) followed by Category IVa (Neoplasm- Benign) accounting for 37%. Pleomorphic Adenoma was the commonest Benign Neoplasm. Malignancy (Category VI) accounted for 11% of FNAC while suspicious for Malignancy (Category V) were 6% case. Diagnostic accuracy of the Milan System was calculated as 88.88%. Cohen Kappa test value 0.81 showed strong agreement between cytology reporting by Milan System and biopsy. Conclusion: The Milan System for Reporting Salivary Gland Cytology should be applied for standardization of salivary gland cytology reporting as there is a good correlation between it and Histopathology, hence are complementary to each other.